Utilizing E-Learning To Develop A Digitally Literate Community In Jayamekar Village, Pakenjeng District - Budiman, Tedi; Rosmini; Sofwan, Ahmad (Badranaya: Jurnal Pengabdian Kepada Masyarakat, 2024)
The appropriate use of digital technology can support the development of digital literacy in Jayamekar Village, Pakenjeng District. This study examines community empowerment through digital literacy by coordinating with the Village Head to understand the village's profile and conditions. An initial survey revealed a low level of digital literacy. The implemented program included creating email accounts and providing digital literacy training. As a result, the community's understanding and skills significantly improved, leading to positive impacts on the promotion and marketing of local products.